Investigation the effect of different surface ligand treatments on luminescence and performance of quantum dot LEDs - Nguyen, Huu Tuan; Duong, Anh Tuan; Lee, Soonil (Journal of Materials Research, 2021)
A series of LEDs that have a green CdSe@ZnS quantum dot (QD) emitting layer (EML) in response to treatment with formic acid (FA), 1,3-benzenedithiol (BDT), and 1,2-ethanedithiol (EDT) were fabricated and investigated. The initial long-chained ligands of oleic acid-based CdSe@ZnS QD layers were partially replaced by short-chained and more conductive ligands of FA, BDT, and EDT that can offer to improve the performance of QD-LEDs (QLEDs). Comparison of the operation characteristics of QLEDs without and with various solution treatments revealed that the control of charge injection and recombination conditions in QD EMLs is the key step for the improvement of the efficiency of our devices. The best device performance was observed for EDT treatment with the maximum luminance and luminous efficiency of 3776 cd m−2 and 1.47 cd A−1, respectively, which are increased by 487% and 270% compared with those of the untreated QLED. Graphic abstract: [Figure not available: see fulltext.]
Keywords: CdSe-ZnS; Device performance; Emitting layer; Luminous efficiency; Maximum luminance; Operation characteristic; Solution treatments; Surface ligands; Devices; Luminescence; Optoelectronic; Quantum dots